1998
DOI: 10.1136/hrt.79.4.412
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency catheter ablation for atrial flutter following orthotopic heart transplantation

Abstract: A 26 year old woman with a diagnosis of limb girdle muscular dystrophy and peripartum cardiomyopathy underwent orthotopic heart transplantation using standard atrial anastomoses. Recurrent atrial flutter was demonstrated in the absence of histological evidence of cellular rejection. Radiofrequency ablation of the flutter circuit was successfully performed allowing the avoidance of long term antiarrhythmic therapy. Ten weeks following ablation and cessation of amiodarone, presyncopal symptoms were found, associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Mapping and ablation of atrial flutter in cardiac transplant recipients using conventional electrophysiologic criteria have been previously reported in single case reports 5–7 and a case series 8 . Electroanatomic mapping of transplant‐associated atrial flutter has been reported in single case reports 1,9,10 and one smaller case series 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Mapping and ablation of atrial flutter in cardiac transplant recipients using conventional electrophysiologic criteria have been previously reported in single case reports 5–7 and a case series 8 . Electroanatomic mapping of transplant‐associated atrial flutter has been reported in single case reports 1,9,10 and one smaller case series 11 .…”
Section: Discussionmentioning
confidence: 99%
“…This study suggested a flutter circuit involving macroreentry around the tricuspid annulus, but the study did not involve detailed electroanatomic mapping of the flutter circuit or ablation of the arrhythmia in the patients. Publications describing successful atrial flutter ablation in transplanted hearts have been limited to single case reports 5–12 . Here we describe detailed electroanatomic mapping and radiofrequency catheter ablation in three patients with right atrial flutter that occurred 8 to 10 years after orthotopic heart transplantation.…”
Section: Introductionmentioning
confidence: 95%
“…This finding is analogous to the proposed mechanism of supraventricular tachyarrhythmias in patients who have undergone extensive atrial surgery for congenital heart disease, such as some forms of the modified Fontan operation, and atrial switch procedures (Mustard or Senning operations) (1–5). In transplanted hearts, where there may be both right and left atrial suture lines, atrial flutter has been noted, mapped to the right atrium, and successfully treated with radiofrequency ablation (11–13). A comparison of patients who had a right atrial anastomosis to those who had bicaval anastomoses for heart Tx yielded a significantly higher incidence of atrial arrhythmias in the group that underwent right atrial anastomosis: only one patient in the bicaval anastomosis group (n = 30) had an atrial arrhythmia, whereas 12 patients in the right atrial anastomosis group (n = 30) had atrial arrhythmias during the follow‐up period (14).…”
Section: Discussionmentioning
confidence: 66%